2022
DOI: 10.1186/s12935-022-02597-9
|View full text |Cite
|
Sign up to set email alerts
|

DNA repair and damage pathways in mesothelioma development and therapy

Abstract: Malignant mesothelioma (MMe) is an aggressive neoplasm that occurs through the transformation of mesothelial cells. Asbestos exposure is the main risk factor for MMe carcinogenesis. Other important etiologies for MMe development include DNA damage, over-activation of survival signaling pathways, and failure of DNA damage response (DDR). In this review article, first, we will describe the most important signaling pathways that contribute to MMe development and their interaction with DDR. Then, the contribution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 107 publications
(126 reference statements)
0
6
0
Order By: Relevance
“…The MAPK ERK1/2 pathway is involved in different cellular processes, e.g., survival and apoptosis, proliferation, differentiation and inflammation, and is often activated in many cancers, including mesothelioma, where it plays a key role in asbestos-induced carcinogenesis [ 31 , 41 ]. Previous studies demonstrated that GHRH antagonist JMR-132 inhibits the growth of human prostate cancer xenografted into nude mice through the inactivation of ERK [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The MAPK ERK1/2 pathway is involved in different cellular processes, e.g., survival and apoptosis, proliferation, differentiation and inflammation, and is often activated in many cancers, including mesothelioma, where it plays a key role in asbestos-induced carcinogenesis [ 31 , 41 ]. Previous studies demonstrated that GHRH antagonist JMR-132 inhibits the growth of human prostate cancer xenografted into nude mice through the inactivation of ERK [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The current review shows that the DDR pathway also seems to be involved in PeM, which is in line with literature on mesothelioma. 28 In almost half of the patients with PeM, BAP1 was altered. BAP1 is involved in multiple processes, including DDR, and acts as a TSG by binding to BRCA1 , another well-known TSG.…”
Section: Discussionmentioning
confidence: 99%
“…We also identi ed mutations in MET, TP53, CDKN2A/2B, and RB1 in more than one tumor. BAP1 has important functions in tumor suppression [33] and has been reported in various cellular processes, including DNA damage response [34,35] , chromosome stability [36] ,…”
Section: Discussionmentioning
confidence: 99%